2018
DOI: 10.1590/s1806-37562017000000129
|View full text |Cite
|
Sign up to set email alerts
|

Is suicidal ideation associated with allergic asthma and allergic rhinitis?

Abstract: Objective:To investigate whether there is an association between suicidal ideation (SI) and allergic diseases in adults. Methods:This was a comparative cross-sectional study involving individuals ranging from 20 to 50 years of age recruited from a university hospital in the city of Guadalajara, Mexico. We included patients with a confirmed diagnosis of allergic asthma, those with a confirmed diagnosis of allergic rhinitis, and healthy controls. All subjects completed the Beck Depression Inventory-II (BDI-II), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…As demonstrated in this analysis, in all study groups the prevalence of symptoms of depression correlated with a decrease in the quality of life in both physical (PCS) and mental (MCS) functioning domains. These results coincide with data obtained in other studies [16][17][18]. In the study by Jones et al [19], depression symptoms assessed on the Hospital Anxiety and Depression Scale (HADS) in bronchial asthma patients showed a higher degree of correlation with quality of life parameters than with lung function parameters.…”
Section: Discussionsupporting
confidence: 89%
“…As demonstrated in this analysis, in all study groups the prevalence of symptoms of depression correlated with a decrease in the quality of life in both physical (PCS) and mental (MCS) functioning domains. These results coincide with data obtained in other studies [16][17][18]. In the study by Jones et al [19], depression symptoms assessed on the Hospital Anxiety and Depression Scale (HADS) in bronchial asthma patients showed a higher degree of correlation with quality of life parameters than with lung function parameters.…”
Section: Discussionsupporting
confidence: 89%
“…SM was also elevated among individuals with SA 150 (45.30%) and considering all individuals with SM, 241 (72,80%) were asthmatic.It indicates that almost three quarters of this group showed disinterest in life. SI were also greater in asthmatics with the severe form of the disease, 35 (47.90%), and was higher among all individuals with asthma, 55 (75.30%), than preceding estimates that varied between 7.6% to 30.4% (10)(11)(12)35,36,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 73%
“…In Korean population-based, nationwide cross-sectional study, AR and/or rhinosinusitis showed a negative impact on quality of life measured EQ-5D questionnaire [29]. Bedolla-Barajas et al [31] in their study estimated that the risk of suicidal thoughts in people with AR reached 11.7% (in the general population the prevalence of this phenomenon was 9.2% [32]), however, when compared with the control group, no correlation was found between AR and the presence of suicidal thoughts. Munoz-Cano et al [33] assesses, other than depression and anxiety with HAD score quality of sleep.…”
Section: Allergic Rhinitismentioning
confidence: 99%